Respostas
respondido por:
30
(x - 2).(x + 5) =
x² + 5x - 2x - 10 =
x² + 3x - 10
x² + 5x - 2x - 10 =
x² + 3x - 10
respondido por:
4
(x-2)(x+5)
x ao quadrado +5x -2x-10=0
x ao quadrado +3x=10
Fator comum em evidência
x(1+3)=10
x=10-1-3
x=7
Não sei se está certo mas espero ter ajudado
x ao quadrado +5x -2x-10=0
x ao quadrado +3x=10
Fator comum em evidência
x(1+3)=10
x=10-1-3
x=7
Não sei se está certo mas espero ter ajudado
respondido por:
1
(x-2)(x+5)
x ao quadrado +5x -2x-10=0
x ao quadrado +3x=10
Fator comum em evidência
x(1+3)=10
x=10-1-3
x=7
Não sei se está certo mas espero ter ajudado
x ao quadrado +5x -2x-10=0
x ao quadrado +3x=10
Fator comum em evidência
x(1+3)=10
x=10-1-3
x=7
Não sei se está certo mas espero ter ajudado
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás